Suitability of the Perceived Motivational Climate in Sport Questionnaire-2 for Dance Research: A Think Aloud Approach. Issue 4 (December 2015) - Hancox, Jennie E.; Quested, Eleanor; Duda, Joan L.
The Perceived Motivational Climate in Sport Questionnaire-2 (PMCSQ-2) adapted for dance has been employed in a variety of dance settings. However, the content validity of the measure and the relevance of particular subscales (e.g., Intra-Team Member Rivalry) have been questioned. Thus, the aims of this study were twofold: first, to examine the content validity of the PMCSQ-2 and identify problematic items and the nature and frequency of such problems experienced by dancers completing the measure; and second, to determine whether the content of task-involving and ego-involving climates, as captured in the subscales of the PMCSQ-2, are relevant and meaningful in dance contexts. Think aloud interviews were conducted with 21 dancers (10 male, 11 female) representing diverse types and levels of dance experience. The interviews were transcribed verbatim and segmented into text related to each item in the PMCSQ-2. Each participant's responses were individually analyzed, with the nature and frequency of problems encountered recorded in relation to five potential causes: errors in understanding, interpretation, retrieval, judgment, and responding. Think aloud interviews revealed that 72% of the participant responses presented no problem, indicating that the measure has an acceptable degree of content validity. However, the findings highlight a number of potentially problematic areas that warrant further attention. Implications for the interpretation of previous research and the conduct of future research employing the PMCSQ-2 in dance as well as other achievement contexts (e.g., sport) are discussed.